The IBD-disk accurately assesses disability and psychological burden at IBD diagnosis and predicts adverse outcomes in both UC and Crohn’s disease during the first year of treatment: a prospective observational cohort study - Rimmer, Peter; Stoica, Viorelia; Ibrahim, Maryam; Javed, Asima; Hazel, Karl; Owusu, Michael; Regan-Komito, Daniel; Cooney, Rachel; Iqbal, Asif J.; Chapple, Iain; Harvey, Philip; Iqbal, Tariq H. (Frontiers in Gastroenterology, 2025)
BackgroundInflammatory bowel disease (IBD) is linked with increased prevalence of mental health disorders (MHD), particularly anxiety and depression. How this influences treatment outcomes in the first year after diagnosis is poorly studied. The IBD disk is a patient-reported outcome measure that quantifies disease-associated disability. Our objectives were to determine if the disk can identify those at risk of adverse treatment outcomes during the first year after diagnosis and assess if it could accurately screen for significant mental health symptoms at IBD presentation.Materials and methodsPatients with suspected IBD were seen in a rapid-access clinic. An IBD disk was completed upon first review, pre-diagnosis. A subgroup simultaneously completed the Hospital Anxiety and Depression scale (HADS). Repeat disks were completed after diagnosis, with 12-month outcomes collected prospectively.Results188 patients completed a baseline IBD disk (97 Crohn’s disease [CD], 91 Ulcerative colitis [UC]), 95 completed a simultaneous HADS and 82 completed a repeat disk after diagnosis and treatment. Pre-existing MHD were more frequent in CD. Pre-diagnosis, the IBD Disk ‘Emotions’ domain correlated with HADS depression (rs=0.607 p<.001), anxiety (rs=0.586 p<.001) and reliably identified HADS defined moderate-severe depression (Area under the curve [AUC] 0.873, 95% CI 0.804 – 0.942). An ‘Emotions’ domain score ≥7 identified all patients meeting this HADS threshold (Sensitivity 100%, specificity 60.5%, Youden’s index 0.601). The strength of discrimination fell post diagnosis (AUC 0.712, 95% CI 0.491 – 0.932), with ongoing high ‘Emotions’ domain scores strongly linked to disease activity in both CD and UC. Elevated baseline disk scores in UC predicted the subsequent need for advanced therapies (p=0.019), persistent active disease at 12 months (p=0.023) and need for inpatient treatment (p<.001). In CD, elevated disk scores predicted need for advanced therapies (p=0.014) and persistent active disease (p=0.015), though an association with the need for surgical resection within 12 months was not statistically significant (p=0.064).ConclusionsThe IBD disk reliably screens for symptoms of depression and anxiety and identifies risk of adverse treatment outcomes at IBD presentation. Particularly in UC, higher disk scores at diagnosis could complement existing tools to better identify those who would benefit from early treatment escalation.